Chronic myeloid leukemia - Hehlmann, Rüdiger (Springer International Publishing, 2021)
Cytogenetics of Chronic Myeloid Leukemia (CML) -- The Biology and Pathogenesis of Chronic Myeloid Leukaemia -- Epidemiology of Chronic Myeloid Leukemia.-Imatinib and the first line CML Therapy -- CML Therapy: A Focus on Second and Third Generation Tyrosine Kinase Inhibitors -- Adverse events associated with ATP-competitive BCR-ABL1 tyrosine kinase inhibitors in chronic myeloid leukemia -- Pharmacoeconomic considerations for tyrosine kinase inhibitors in the treatment of chronic myeloid leukemia -- Standardization of molecular monitoring for chronic myeloid leukemia: 2021 update -- Prognostic Scores for Patients with Chronic Myeloid Leukemia under Particular Consideration of Disease-Specific Death -- A Review and an Update of European LeukemiaNet Recommendations for the Management of Chronic Myeloid Leukemia -- The Role of Hematopoietic Stem Cell Transplantation in CML -- CML end-phase and blast crisis: implications and management -- The Interferon-alpha Revival in CML -- Managing Pregnancy in Chronic Myeloid Leukemia -- Response-Related Predictors of Survival and of Treatment Free Remission in CML -- Discontinuation or cessation of tyrosine kinase inhibitor treatment in Chronic myeloid leukemia patients with deep molecular response. .